Meningkatkan Hasil Belajar Siswa Melalui Model Pembelajaran Learning Together Pada Mata Pelajaran Pai Kelas IV Di SD Swasta Perguruan Swakarya - Azizah Lolo Banta Padang; Ramadhani Siregar; Uswatun Hasanah; Shafira Nur Permana; Rifqih Fernanda (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2024)
The purpose of this study is to reveal the effect of cooperative learning learning together model on learning outcomes of Islamic Religious Education and to find out how far the understanding and mastery of Islamic Religious Education subjects after the implementation of cooperative learning learning together model. This study used two rounds of action research. Each round consists of four stages: design, activity and observation, reflection, and revision. The target of this research is students of Class IV of Private Elementary Schools of Swakarya College. The data obtained is in the form of formative test results, observation sheets of teaching and learning activities. From the results of the analysis it was found that student achievement increased from cycle I to cycle II, namely, cycle I (75.00%), cycle II (85.00%).